POTENSI PEMANFAATAN LIMBAH PEMBAKARAN BATUBARA (BOTTOM ASH) PADA PLTU SEBAGAI MEDIA TANAM DALAM UPAYA MENGURANGI PENCEMARAN LINGKUNGAN - Redaksi Tim Jurnal (KILAT, 2018)
The impact of environmental pollution is now beginning to perceive by all levels of humans and in the world such as global warming, until climate change has inspired the research on the utilization of waste coal combustion (Bottom Ash) power plant. This research uses Bottom Ash (BA) from PLTU (Electric Steam Power Plant) Suralaya, by choosing Selada (Lactuca sativa), Sawi (Ipomea Autica), and Kangkung (Brassica rapa var). Percentage BA used as planting media is 0%, 25%, 50%, 75%, and 100%. BA serves to accelerate the process of rupture and plant growth due to the availability of Ca, Mg, Na, K, N, P, S and Fe elements. Planting media for Lettuce plant species is 25%. The corresponding percentage of BA as planting media for Plant Sawi species is 25%, and 50%. While in the Kangkung plant BA percentage that is suitable for use as a planting media is 25%, 50%, and 75%. The apparent anomaly at this test are Kangkung percentage 75% and Lettuce50%, 75% stems become longer, and leaves become slightly even in 100% Bottom Ash percentage, Lettuce grows with smaller size/dwarf. The amount of nutrient excess need to be accurately measured through laboratory test first. With further testing it is hoped that the utilization of coal ash waste (Bottom Ash) becomes more real and effective as a growing media seen from risk and danger aspects.